Edukasi Kewirausahaan di Desa: Membentuk Karakter Wirausaha Pada Anak Melalui Simulasi Berdagang - Khairunnisa Salsabila Putri Prameswari; Utami Puji Lestari; Eli Masnawati; Nurul Masithoh; Ella Anastasya Sinambela; Eli Retnowati; Mirza Elmy Safira (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
children are the successors of the family and the nation. In Kedung Jumputrejo Village, Sukodono Subdistrict, the development is very dense which requires the community to compete to continue living. This community service focuses on introducing the concept of trading to foster an entrepreneurial spirit. The main objective of this community service is to introduce the concept of trading to children or santri at TPQ Alif Lam Mim, Kedung Jumputrejo Village, Sukodono District with the aim of fostering an entrepreneurial spirit from an early age. The strategy method in this community service is Asset Based Community Development (ABCD). The results of the service showed that there were children's characters who began to dare to express opinions in negotiations based on what they wanted to get and began to grow their interest in entrepreneurship which was reflected in their enthusiasm.